X-Ray Diffraction Studies of Co(II) Complexes with Hydroxy Oximes - G. Kelkar, Jitendra; Mehta, B.H. (Asian Journal of Chemistry, 2010)
Oximic ligands were synthesized using 2-hydroxy-1-naphthaldehyde and 2,4-dihydroxyacetophenone. Co(II) complexes of these oximes were synthesized having metal : ligand stoichiometry 1 : 2. The ligands and the complexes were diagnosed for their analytical parameters and various spectral features. The structures of these complexes were proposed on the basis on electronic absorption spectra, magnetic susceptibility. The lattice parameters were calculated using X-ray powder diffraction data.